Authorship and Contributorship in Publication Ethics and Guidelines: The Publishers’ Perspective - Khattri, Man Bahadur; Subedi, Madhusudan; Pandey, Rishikesh; Bhandari, Prem (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Authorship and contributorship are among the most important, sensitive, and complex areas of academia and thus demand critical awareness among the authors, editors, and readers.